Determining the Role of Amylase Enzyme Activity in Growth of Fish - M. Abareethan; A. Amsath (Research Aspects in Biological Science Vol. 3, 2022)
In the present study, the genomic DNA of probiotic isolates from the gut and the gene sequence responsible for enzyme activity of Labeo rohita were analyzed. Probiotics are beneficial microbial populations that improve the growth and immunity of fish under challenging environmental conditions by modifying probiotic bacterial strain gut colonisation. The studies were carried out by mixing the strain with water and supplementing it with commercial feed for Labeo rohita development. Only two strains had better activity, according to the results. The genomic DNA of these isolated probiotic microorganisms was analysed and electrophoresed to establish their taxonomic identity using Universal 16S primers. The isolates’ 16S rRNA sequences were amplified using primers and PCR. The isolated probiotic microorganism’s genomic DNA was analysed using Universa 16S primers and electrophoresed to confirm the taxonomic identity. The 16S rRNA sequence of the isolates was amplified using primers using PCR. Blast analysis of 16S rRNA sequence was carried out with the sequences available in the NCBI database. Amylase, protease, and lipase enzymes significantly boost probiotic activity by enhancing water quality indicators, food absorption, and L. rohita growth. The effect of the found strain on fish growth was investigated, and it was suggested that it may be used to improve L. rohita fish growth.